PENINGKATAN MOTORIK HALUS ANAK USIA DINI MELALUI TEKNIK PILIN KERTAS (TPK) UNTUK PENDIDIK - Sugiana, Sugiana; Prasetyo, Tommy Rizki; Irzalinda, Vivi; Nawangsasi, Devi (DEVOSI, 2022)
This workshop aims to provide training in coiling techniques for Early Childhood Education teachers to improve teacher skills in providing learning activities to improve fine motor skills for early childhood. Specifically, the objectives of this training are to 1) Help teachers in Early Childhood Education institutions to improve their ability to arrange learning activities related to fine motor skills, 2) Help teachers in Early Childhood Education institutions to develop their potential by creating innovative activities using the Pilin method, 3) Assisting teachers in developing their abilities related to the twisting method, 4) To find out the description of the fine motor level of teachers in Early Childhood Education institutions through the Paper Pilin Technique. The method chosen in this service activity is to provide assistance training in coiling techniques, either through counseling, discussions, simulation exercises, and giving assignments. The training is carried out in several stages, namely, socialization, implementation stage, and evaluation. The target of the activity is 30 kindergarten teachers in Bandar Lampung City. Service is carried out online. The results of this Community Service can be concluded that the improvement of fine motor skills in early childhood through the Paper Pilin Technique is very effective. This can be explained by the difference in the results of the mean on the pretest and posttest. This means that there is an increase in the knowledge and skills of kindergarten teachers regarding the improvement of fine motor skills in early childhood.